JAKET MULTIFUNGSI âVICTORYâS BAGâ (BARANG BEKAS KAYA KREATIVITAS) - Saputra, Herwiyanda Surya; Verrysaputro, Exwan Andriyan; Wibowo, Wisnu Broto; Pujiono, Tomi (Program Kreativitas Mahasiswa - Kewirausahaan, 2013)
This entrepreneurship field-Student Creativity Program aims to create designs and to produce a multifunctional Jacket "Victorys Bag" (Creativity-Rich Used Goods) and find out its marketing strategies in order to get the big profit. There are several phases in the implementation of this program; those are the market survey, the production, and the marketing. "Victorys Bag" is a result of fusing two used goods-substances; those are jeans patchwork of used jackets and bags which has gone through modification process so that it can be used at the same time, in other words it becomes a Multifunction Bags-Jackets. The expected turnover of this entrepreneurship program is earning Rp. 3.500.000,- in a month of the implementation program; and will grow forward for the following month.